Tinnitus, Equilibrium Disorders, and Anxiety in COVID-19 - Selin Eroğlu; Doğa Turhanoğlu; Sude Naz Büyüksaraç; Doğa Türkü Doğancı; Pelin Deniz; Pelin Koçdor (The Turkish Journal of Ear Nose and Throat)
Objective: Researchers have previously investigated the connection between COVID-19 and equilibrium disorders (ED) and tinnitus. The present study aims to investigate the prevalence of tinnitus and ED in people post-treatment after being positive for COVID-19 and the association of these symptoms with Anxiety and demographic features. Material and methods: Patients from two tertiary hospitals with positive reverse transcription-polymerase chain reaction (RT-PCR) tests for SARSCOV-2 between August 2020 and May 2021 were contacted by phone. The recruited patients were asked to complete our questionnaire over the phone, a developed Turkish version of a previously applied ‘10-item close-ended questionnaire’ by Viola et al. Results: Sixty-two patients experienced ED before COVID-19 (8%). After COVID-19, the incidence of ED sufferers increased to 178 (22%), which was statistically significant (p=0.001). 110 (25.28%) of 435 female patients and 68 (18.37%) of 370 male patients had post-COVID ED. It was significantly more common in women among COVID-19 survivors (p=0.019). The number of patients who experienced tinnitus before COVID-19 was 64 (7%) and 105 (13%) after COVID-19. It was found statistically significant that the tinnitus increased after COVID-19 (p=0.001) Beck’s Anxiety Inventory ( BAI) scores were significantly higher in the post-COVID ED and post-COVID tinnitus sufferers (p=0.001, p=0.047). Conclusions: COVID-19 survivors had significantly suffered tinnitus or ED. BAI scores were significantly higher in post-COVID ED and tinnitus sufferers. So, it can be said that the patients with high Anxiety experienced more tinnitus and ED post-COVID period.